USP1 links platinum resistance to cancer cell dissemination by regulating Snail stability - Sonego, Maura (Sci Adv, 2019)
Resistance to platinum-based chemotherapy is a common event in patients with cancer, generally associated with tumor dissemination and metastasis. Whether platinum treatment per se activates molecular pathways linked to tumor spreading is not known. Here, we report that the ubiquitin-specific protease 1 (USP1) mediates ovarian cancer cell resistance to platinum, by regulating the stability of Snail, which, in turn, promotes tumor dissemination. At the molecular level, we observed that upon platinum treatment, USP1 is phosphorylated by ATM and ATR and binds to Snail. Then, USP1 de-ubiquitinates and stabilizes Snail expression, conferring resistance to platinum, increased stem cell–like features, and metastatic ability. Consistently, knockout or pharmacological inhibition of USP1 increased platinum sensitivity and decreased metastatic dissemination in a Snail-dependent manner. Our findings identify Snail as a USP1 target and open the way to a novel strategy to overcome platinum resistance and more successfully treat patients with ovarian cancer.